The Mediating Role of Mobile Banking-Based Financial Inclusion Disclosure on the Relationship Between Foreign Investment and Bank Performance - Omar Ikbal Tawfik; Mohammed Ali Ahmed; Hamada Elsaid Elmaasrawy (International Journal of Financial Studies)
Purpose: This study aims to demonstrate the impact of Foreign Investment (FI) on the disclosure of digital Financial Inclusion (FIN) through mobile banking (MB) and the performance of banks, as well as the direct impact of disclosing digital FIN indicators through MB on bank performance. Design/methodology/approach: This study utilized actual data from all banks listed on the stock exchange in the Sultanate of Oman between 2015 and 2023. The hypotheses were tested using the partial least squares structural equation model (PLS-SEM). Findings: This study revealed a positive influence of FI on both bank performance and the disclosure of FIN indicators through MB. It also identified a negative effect of disclosing FIN indicators through MB on bank performance. However, the mediation of the disclosure of FIN indicators through MB did not show any impact of FI on bank performance. Practical Implications: This study’s results offer valuable insights and recommendations. Firstly, for bank managers, it is crucial to find a balance between expanding MB services and enhancing bank profitability by studying customer trends and preferences in MB usage. This approach will aid in offering banking services that retain existing customers and attract new ones, ultimately boosting bank profitability. Secondly, for policymakers and regulators, this study enhances the understanding of current practices in disclosing FIN indicators through MB, which may prompt a reevaluation of accounting standards related to traditional and digital FIN indicator disclosure. Originality/value: This study is groundbreaking in its examination of the influence of FI on the disclosure of digital FIN indicators through mobile banking. It also represents the first investigation into the indirect impact of FI on banks’ financial performance (FP) through the disclosure of digital FIN indicators via mobile banking.